2005
DOI: 10.1038/sj.ijo.0802785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term high dietary calcium intake on 24-h energy expenditure, fat oxidation, and fecal fat excretion

Abstract: BACKGROUND:Observational studies have shown an inverse association between dietary calcium intake and body weight, and a causal relation is likely. However, the underlying mechanisms are not understood. OBJECTIVE: We examined whether high and low calcium intakes from mainly low-fat dairy products, in diets high or normal in protein content, have effects on 24-h energy expenditure (EE) and substrate oxidation, fecal energy and fat excretion, and concentrations of substrates and hormones involved in energy metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
190
3
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(218 citation statements)
references
References 21 publications
13
190
3
12
Order By: Relevance
“…Conversely, decreased dietary calcium intake may lead to increased intracellular calcium levels, which in turn may trigger an increase in lipogenesis and body fat. 20 Another possible mechanism by which calcium intake reduces BMI would be by increased fecal fat excretion, as recently suggested by Jacobsen et al 24 This study has several limitations: height and weight were self-reported, leading to a possible underestimation of overweight and obesity. 25,26 Still, reported height and weight data have been used in other epidemiological studies 27 and the bias is conservative, since overweight or obese subjects (misclassified as normal or overweight, respectively) would tend to decrease milk consumption in normal and overweight groups, thus decreasing the magnitude of the observed differences.…”
Section: Discussionmentioning
confidence: 81%
“…Conversely, decreased dietary calcium intake may lead to increased intracellular calcium levels, which in turn may trigger an increase in lipogenesis and body fat. 20 Another possible mechanism by which calcium intake reduces BMI would be by increased fecal fat excretion, as recently suggested by Jacobsen et al 24 This study has several limitations: height and weight were self-reported, leading to a possible underestimation of overweight and obesity. 25,26 Still, reported height and weight data have been used in other epidemiological studies 27 and the bias is conservative, since overweight or obese subjects (misclassified as normal or overweight, respectively) would tend to decrease milk consumption in normal and overweight groups, thus decreasing the magnitude of the observed differences.…”
Section: Discussionmentioning
confidence: 81%
“…The mode of action may be through a decrease in the intracellular Ca 2 þ levels in adipocytes, followed by a decrease in lipogenic gene expression and activity, thereby promoting lipolysis (Zemel et al, 2000;Zemel, 2002;Parrikh & Yanovski, 2003). Furthermore, some studies suggest that dietary calcium can bind fatty acid in the gut and thereby decrease fat absorption (Welberg et al, 1994;Jacobsen et al, 2005). However, there are some inconsistencies in the evidence of the weight-reducing effect of calcium, (Barr, 2003) and further studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, based on results showing that women consuming less than 600 mg calcium/d had an increased percentage body fat (4) , the existence of a threshold of usual calcium intake below which a supplementation in this mineral would effectively promote fat mass loss is possible. The first objective of the present study was to investigate this hypothesis and to assess the impact of a calcium plus vitamin D (calciumþD) supplementation on the outcome of a weightreducing programme in female low-and very low-calcium consumer (VL-CC) overweight/obese subjects.Up to now, the potential effect of calcium on energy balance and adiposity has been explained by a suppression of calcitriol (1,25-dihydroxyvitamin D) which decreases intra-adipocyte calcium influx and concentration (5) leading to a reduced lipogenic gene expression and stimulation of lipolysis and adipocytes uncoupling protein 2 expression (6,7) .Moreover, a diet high in calcium was also shown to increase 24 h lipid oxidation (8) and to reduce lipid absorption due to the intestinal formation of calcium-fatty acids insoluble 'soaps' that are excreted in the faeces (9) . From another perspective, the idea of a 'calcium-specific appetite control' was proposed by Tordoff (10) who documented the possibility that low calcium intake or stores might trigger episodes of increased desire to eat and stimulate motivation to seek out or choose calcium-containing items, and potentially other nutrients and/or food 'recognised' as calcium-rich (10) .…”
mentioning
confidence: 99%
“…Moreover, a diet high in calcium was also shown to increase 24 h lipid oxidation (8) and to reduce lipid absorption due to the intestinal formation of calcium-fatty acids insoluble 'soaps' that are excreted in the faeces (9) . From another perspective, the idea of a 'calcium-specific appetite control' was proposed by Tordoff (10) who documented the possibility that low calcium intake or stores might trigger episodes of increased desire to eat and stimulate motivation to seek out or choose calcium-containing items, and potentially other nutrients and/or food 'recognised' as calcium-rich (10) .…”
mentioning
confidence: 99%